Diet culture mindset and meat restriction: A mixed methods mediation analysis - Marina F. Jiao; Saadatu Abdul-Rahaman; Michelle Leonetti; Lizzy Pope; Kelsey Rose; Emily H. Belarmino (The Journal of Climate Change and Health, 2025)
Introduction: Reducing meat consumption and eating a “plant-based diet” is recommended to improve health and environmental outcomes including reducing climate change. One understudied aspect of this dietary recommendation is how it may intersect with diet culture, which equates thinness to health. The purpose of this study is to explore the relationship between diet culture beliefs and meat limitation, and the potential mediating role of dietary motivation. Methods: This mixed methods study involved a national U.S. survey of 2,750 rural adults and interviews with 28 adults in Vermont, U.S.A. who limit meat intake. Survey respondents were asked about their dietary pattern, dietary motivations, and beliefs about “good” vs. “bad” foods and fatness. Responses were analyzed using mediation models. Interviews focused on perceptions of and experiences with plant-based eating. Transcripts were thematically coded and analyzed for diet culture beliefs. Results: Moralizing food and meat limitation were closely related. Health motivations fully mediated the relationship, while weight motivations partially mediated the relationship. Anti-fat beliefs were not related to meat limitation. Over half of interview participants imparted a moralization of “good” vs “bad” onto foods and nearly half discussed the healthfulness of plant-based diets and meat limitation. Conclusion: These results suggest that food moralization and meat limitation are related, and that individuals’ motivations to lose weight and be healthy may mediate the relationship. Although plant-based diets have potential health and environmental benefits, framing these dietary patterns around restriction may adversely affect eaters’ relationships with food. Further research with more diverse samples is needed.